Hospitalisation costs of malignant mesothelioma: results from the Italian hospital discharge registry (2001–2018) - Pierpaolo Ferrante (BMJ Open)
Objectives This paper aims to establish hospitalisation costs of mesothelioma in Italy and to evaluate hospital-related trends associated with the 1992 asbestos ban.Design This is a retrospective population-based study of Italian hospitalisations treating pleura, peritoneum and pericardium mesothelioma in the period 2001–2018.Settings Public and private Italian hospitals reached by the Ministry of Health (coverage close to 100%).Participants 157 221 admissions with primary or contributing diagnosis of pleural, peritoneal or hearth cancer discharged from 2001 to 2018.Primary and secondary outcome measures: number, length and cost of hospitalisations with related percentages.Results Each year, Italian hospitals treated a mesothelioma in 6025 admissions on average. Mean annual costs by site were €20 293 733, €3183 632 and €40 443 for pleura, peritoneum and pericardium, respectively. Pericardial mesothelioma showed the highest cost per admission (€6117), followed by peritoneal (€4549) and pleural cases (€3809). Percentage of hospitalisation costs attributable to mesothelioma was higher when it is located in pleura (53.4%) and pericardium (51.8%) with respect to peritoneum (41.2%). Overall annual hospitalisation cost, percentages of number and length of admissions showed an inverted U-shape, with maxima (of €25 850 276, 0.064% and 0.096%, respectively) reached in 2011–2013. Mean age at discharge and percentages of surgery and of urgent cases increased over time.Conclusions The highest impact of mesothelioma on the National Health System was recorded 20 years after the asbestos ban (2011–2013). Hospitals should expect soon fewer but more severe patients needing more cares. To study the disease prevalence could help assistance planning of next decade.